(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The opioid crisis, which is still taking lives at a never-before-seen rate and causing a devasting array of avoidable morbidity, is one of the worst failings of our contemporary healthcare system. This issue has developed over several decades, even if the availability of extremely powerful synthetic opioids has increased the crisis’s urgency for both patients and communities. Because of their wide accessibility, in-depth medication knowledge, and integration into a variety of healthcare settings, chemists are in a position to provide numerous viable answers. Pharmacists have the ability to combat the opioid issue with purposeful and effective actions. While some chemists may start by carefully considering the language they use when speaking to and discussing patients with substance use disorders, others may be in a position to introduce novel and extensive pharmacist-led therapeutic services. In order to maximize patient results, it is imperative to tackle the ineffectual laws, regulations, and policies that adversely affect pain and addiction treatment. This will enable the widespread dissemination of evidence-based treatments. It is imperative that chemists take a strong stance in favor of eliminating regulations that hinder advanced clinical treatment or that support patient abuse and desertion. In order to deploy resources effectively, there should be support for ongoing research on pain and opioid use disorder treatments and services, as well as the effects of harm reduction techniques and pharmacist-led clinical services.